Calculation of Sectio Caesarea Action Rates Using Activity Based Costing (Abc) System Method in Anutapura Palu General Hospital - Ridwan, Riska Yuliana; Ashari, Muhammad Rizki (Journal of Health Education and Literacy, 2021)
Operating room service is one of the profit centers that have high leverage for hospital revenue. In determining the tariff, Anutapura Public Hospital of Paluuses a double distribution which is a conventional method. The double distribution method has many shortcomings which results in inaccurate unit cost calculations due to cost distortion. A decrease in income and an increase in total operational costs can interpret that the hospital has a deficit because the costs incurred are not in accordance with the activities that occur in the service. Activity Based Costing (ABC) is a calculation of costs based on activity and overhead costs based on each cost driver. The purpose of this research was to calculate the amount of tariffs on the section caesarea action at Anutapura Public Hospital of Palu using the Activity Based Costing (ABC) System. Type of the research was quantitative research with a descriptive approach to data processing systems using a computerized system. In this research, the cost driver used the duration of action and floor area. The results show that the tariffs of Caesarean Sectio action using the Acitivity Based Costing method are Class III Rp. 8,984,697, Class II Rp 9,493,643, Class I Rp 9,945,730, and VIP Class Rp 10,913,873. For Anutapura Public Hospital of Palu, it is recommended to use Activity Based Costing (ABC) calculation as a comparison in determining tariffs.